ANALISIS SIFAT MEKANIK BAJA SKD 61 DENGAN BAJA ST 41 DILAKUKAN HARDENING DENGAN VARIASI TEMPERATUR - Nofri, Media; Taryana, Acang (Bina Teknika, 2017)
The alloy steel that is widely used in the world of manufacturing industry is the type of tool steel because it has special characteristics and includes special steel. One type of tool steel that is widely used by the manufacturing industry is SKD steel type 61. ST 41 steel material is a low carbon steel with a carbon content of 0.08% -0.20%. ST 41 steel is commonly used as industrial machine component, but in this ST 41 steel is not as strong as steel SKD 61. So, to improve quality to ST 41 steel. Quality improvement can be done by heat treatment process. To obtain hardness requires the heating process, holding time, cooling medium, precise hardening temperature and see the material comparison between SKD 61 steel and ST 41 steel before and after the hardening process to the nature of hardness and microstructure. Result of hardness test of SKD 61 nonheattreatment steel material has hardness value equal to 197 HV, ST 41 nonheatreatment steel material has hardness value equal to 165 HV, after hardening for temperature 900⁰C has hardness value 154 HV, temperature 950⁰C has hardness value 152 HV, temperature 1000⁰C has 161 HV magnification value. Seen in the metallographic results appear to be a change in microstructure on ST 41 steel which after the hardening structure looks more dominant after the hardening structure turned into bainite-ferrit